2012
DOI: 10.2527/jas.2011-4276
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by region and season interactions on weaning weight in United States Angus cattle1

Abstract: The objective of this study was to determine if weaning weight performance is genetically consistent across different environments in the United States. The American Angus Association provided weight and pedigree data. Weaning weights observed in the Southeast (SoE) and Northwest (NW) were the focus of this study, as these regions are perceived as opposite extremes in climate. The 2 most represented calving seasons in each region were fall and winter in the SoE and winter and spring in the NW. The original dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The low correlation of the southern regions (the South, the Desert, and the Gulf Coast) with the northern regions (the Mountains, the Northeast, the Pacific, and the Upper Plains) agrees with Williams et al (2012a), Williams et al (2012b) suggest the differences in weights observed between regions and seasons may be complex. For example, calves born in smaller contemporary groups in the Southeastern United States may perform better than expected due to increased care over calves from larger contemporary groups.…”
Section: Genetic Correlations Between Regionsmentioning
confidence: 67%
“…The low correlation of the southern regions (the South, the Desert, and the Gulf Coast) with the northern regions (the Mountains, the Northeast, the Pacific, and the Upper Plains) agrees with Williams et al (2012a), Williams et al (2012b) suggest the differences in weights observed between regions and seasons may be complex. For example, calves born in smaller contemporary groups in the Southeastern United States may perform better than expected due to increased care over calves from larger contemporary groups.…”
Section: Genetic Correlations Between Regionsmentioning
confidence: 67%
“…The estimate for WW was similar to that of Winder et al (1990) but much higher than that of Speidel et al (2005). Williams et al (2012b) reported heritability estimates of 0.28 and 0.26 for WW, with greater heritability in low altitudes. Heritability estimates tend to be lower in field data compared with designed studies due to uncontrolled environmental sources of variation (Bertrand et al, 1985).…”
Section: Heritability Of Birth Weight and Weaning Weightmentioning
confidence: 98%
“…Bertrand et al (1985) reported significant differences in sire × region effects in Polled Hereford field data (range from 0.39 to 1.0). Williams et al (2012b) explored G×E between high and low altitudes and found a correlation of 0.74. Buchanan and Nielsen (1979) analyzed Simmental and Maine-Anjou field data and reported significant sire × region effects.…”
Section: Genetic Correlations Between Regionsmentioning
confidence: 99%
“…Earlier studies have reported the existence of significant G×E in growth traits between production systems (Bradfield et al, 1997;Amelie, 2007;Assenza et al, 2010;Raidan et al, 2015), among regions (Van Niekerk et al, 2004;Guidolin et al, 2012;Bresolin et al, 2015), between countries (Espasandin et al, 2011) and between seasons of birth (De Alencar et al, 2005;Williams et al, 2012). For example, Assenza et al (2010) found that the genetic correlations between each trait expressed in an intensive fattening system and the same trait expressed in a pasture spanned from 0.31-0.93 while Raidan et al (2015) reported genetic correlation to be 0.75 for final weight between nellore cattle reared in feedlot and on pasture.…”
Section: Introductionmentioning
confidence: 98%
“…Identification of genotype-environment interaction in beef cattle may help the artificial selection process and increase the efficiency of genetic evaluation on sires submitted to different environments (Guidolin et al, 2012). Identification of environmental factors important in G×E and identification of animals best suited for given environment will help producers in making optimal decisions given their management setting (Williams et al, 2012). The G×E means simply that the effect of the environment on different breeds or genotypes is not the same; this implies that there is no universally "Best" genotype; the best genotype will vary from one environment to another and will depend on the prevailing environment conditions.…”
Section: Introductionmentioning
confidence: 99%